Plant Genebanks: Present Situation and Proposals for Their Improvement. the Case of the Spanish Network - Díez, María José; De la Rosa, Lucía; Martín, Isaura; Guasch, Luís; Cartea, María Elena; Mallor, Cristina; Casals, Joan; Simó, Joan; Rivera, Ana; Anastasio, German; Prohens, Jaime; Soler, Salvador; et al. (Frontiers in Plant Science, 2018)
Genebanks were created in the middle of the twentieth century to preserve cultivated biodiversity when landraces began to be substituted by modern varieties. This move was generally accepted as a necessary step to safeguard the future. After about 75 years of collecting and maintaining genetic resources, biotechnology’s increasing ability to create new variability brings the roles of genebanks in the present and near future into question. As a continuation of several workshops that started in 2014, staff of some representative genebanks have met to discuss how the Spanish Plant Genetic Resources Network can be improved, identifying the following major shortcomings: lack of efficient coordination in the distribution of species among genebanks; plethora of genebanks; detected and undetected duplicates; insufficient rate of regeneration; insufficient phenotyping, genotyping, and epiphenotyping; unsatisfactory rate of use by end users; and insufficient funding. As a considerable increase in public funding is unlikely, we propose some strategies to increase the efficiency of the system. The most urgent tasks are to strengthen the rationalization of the network by establishing a clear hierarchy and functions, to improve the information of the accessions in the base collection by deep characterization including not only by phenotype but also by uses and utilities, to progressively replace the active collections with focused core collections constructed to meet users’ needs, to optimize regeneration protocols, to limit new collecting expeditions of Spanish crop wild relatives to those growing in threatened habitats, and to develop user-friendly platforms to access germplasm documentation, including a unified system of descriptors and classification categories. Current advances in biotechnology, especially in gene editing, forecast an uncertain future where it is no longer clear whether it is necessary to conserve all existing genes or all the combinations of genes. So we need to find new roles for genebanks (educational, natural history preserves, etc.) and to justify their existence through increased use of the germplasm they hold. At an international level, we need to efficiently balance the variability preserved in banks and the variability created in laboratories, just as we have done with classical and molecular breeding despite initial reluctance.